Analysis Of The Cognitive Level Of Competency Test Questions In Junior High School Mathematics Textbooks Based On The Revised Bloom Taxonomy - Giawa, Freddy; Siregar, Jodi Mahmud; Armanto, Dian (JURNAL JENDELA PENDIDIKAN, 2023)
Cognitive ability is one of the substantial things in learning mathematics so that textbooks which act as the main source of learning should encourage the development of students' cognitive abilities and learning goals. The aim of this research is to describe the results of the cognitive level analysis of junior high school mathematics textbooks for class VII semester I based on the revised Bloom's Taxonomy and numeracy. The type of research used is descriptive research. Data was collected by recording and coding the contents of the book which focused on example questions, Let's Practice questions and Competency Test questions. The data analysis technique uses descriptive statistics. The results of the research show that there are several existing literature studies that the cognitive level analysis of competency test questions in mathematics books must be revised so that students can understand the mechanism of questions according to the reading material regarding the contents of the book. The questions contained in textbooks do not contain a good proportion between each cognitive level, and there are still few numeracy questions involving personal, social or scientific contexts.